A New Topology Via a Topology - DAĞCI, FİKRİYE İNCE; Çakallı, Hüseyin (American Institute of Physics Inc., 2022)
In this extended abstract, we modify the definition of h-open set introduced in [1] by F. Abbas who neglects that the set of all h-open sets is a topology, and we show that the union of any family of h-open subsets of X is h-open that ensures that the set of all h-open subsets of a topological space (X, τ) forms a topology which is finer than τ, where a subset A of a topological space (X, τ) is said to be h-open if A ⊆ Int(A ∪ U) for every non-empty subset U of X such that U ∈ τ. We also give continuity type theorems. © 2022 American Institute of Physics Inc.. All rights reserved.
5th International Conference of Mathematical Sciences, ICMS 2021
Keywords: Continuity; Open Set; Topological Space